That nothing may be lost: fragments and the New Testament text : papers from the Twelfth Birmingham Colloquium on the Textual Criticism of the New Testament - Bates, Clark R.; Marcon, Jacopo; Patton, Andrew J.; Scieri, Emanuele (Texts and studies, 2022)
The manuscript tradition of the New Testament is built upon the foundations of fragmentary material. Whether it be the majority of papyrus documents, the abbreviated citation of biblical material in early Christian writings, or the scattering of once-whole manuscripts across time and space, the story of the New Testament is a gathering of fragments-in all their forms-in the hopes that "nothing may be lost." This present volume is a result of the Twelfth Birmingham Colloquium on the Textual Criticism of the New Testament, wherein presenters were invited to approach the theme of "fragments" from any philological or philosophical framework. Chapters discuss the possible forgery of a biblical papyrus, the dismemberment of a sixteenth-century lectionary manuscript, and the Arabic text of Romans preserved in a fragmentary bilingual codex. Elsewhere, software tools are employed to re-assess the readings of manuscripts digitised in decades past and to join multiple manuscripts together through a relational stemma. Further contributions consider the fragments of the biblical text-both as lemmatic additions to commentaries and stand-alone portions of the biblical text-contained in patristic commentaries and Byzantine catenae. The wide-ranging scope of the research contained in this volume reflects the value of this fragmentary history of the New Testament and the need continually to examine these pieces of the past so that the shape of research in the present accurately illustrates the tapestry that is the history of the New Testament texts